Detection and molecular characterization of leptospira spp. from environmental samples in Kelantan - Azali, Muhammad Azharuddin (2015)

(untitled)
Leptospirosis is an important worldwide zoonotic disease caused by pathogenic leptospires. In Malaysia, Leptospira spp. have been detected in humans, livestock, environmental samples and rodents. Saprophytic species was usually associated with the environment. However, a novel pathogenic species, Leptospira kmetyi has been isolated from the soil in Malaysia. Therefore, the aim of this study is to isolate Leptospira spp. from the soil and water in selected environment, to detect the pathogenic isolates and to determine their genetic relationship. This is a cross-sectional descriptive study. Soil and water samples were collected from well known markets and recreational areas in Kelantan. All samples were filtered and inoculated into modified Ellinghausen and McCullough medium supplemented with additional 5-fluorouracil. The cultures were incubated at 30°C for 30 days and examined under dark field microscope. Microscopic Agglutination Test (MAT) was performed to determine the serovar of the positive cultures. Positive cultures were then subjected to PCR using G1/G2, B64-I/B64-II and Sapro1/Sapro2 primers. The presence of virulence gene lipL32 was also determined. Partial sequences of 16S rRNA gene of the isolates were obtained for molecular identification of the isolates. Phylogenetic analysis was carried out to determine the genetic relatedness among isolates. A total of 144 samples comprised of water (market, n=36; recreational area, n=36) and soil (market, n=36; recreational area, n=36) were collected. Based on darkfield microscopic observations, 10% water and 36% soil cultures were positive for Leptospira spp. All isolates were negative for the hyperimmune sera tested in MAT. A total of 18 out of 33 cultures gave positive PCR assay results using G1/G2 and B64-I/B64-II primers. LipL32 gene was not detected in all of the isolates. 16S rRNA sequencing results showed that 31 out of 33 isolates were identified as Leptospira spp. There were one pathogenic species, Leptospira alstonii and eight intermediate species, L. wolffii (n=7), and L. licerasiae (n=1). Twenty two isolates were identified as nonpathogenic species, L. meyeri. The remaining two isolates were identified as species from other closely related genus, Leptonema illini. Based on phylogenetic analysis, the leptopsiral isolates were clearly separated to form three major clades namely pathogenic, intermediate and nonpathogenic clades. In conclusion, only one pathogenic leptospires, L. alstonii was isolated from environment in selected areas in Malaysia. The remaining isolates were intermediate and saprophytic groups. All isolates were found not to contain one of the highly conserve putative leptospiral virulence gene LipL32.